2009 IEEE International Conference on Systems, Man and Cybernetics 2009
DOI: 10.1109/icsmc.2009.5346943
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and perceptual analyses of human foot movements in pedal operation

Abstract: Abstract-A human can maneuver mechanical systems by adjusting his/her own body naturally and effectively according to a target task by utilizing the kinematical and dynamic characteristics of operating systems acquired through sensory organs. If such human sensory and motor characteristics changing in the task can be quantitatively described, it would be useful to design and develop a novel human-machine system so that humans can manipulate a machine more instinctively and comfortably. This paper investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…There were three different actions when operating the accelerator pedal; HP, R and FP. According to the literature and supported with the findings in this study, the GM muscle plays important role when operating the pedal in driving task [14][15]. In this study, the highest muscle response at GM muscle was at FP action.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…There were three different actions when operating the accelerator pedal; HP, R and FP. According to the literature and supported with the findings in this study, the GM muscle plays important role when operating the pedal in driving task [14][15]. In this study, the highest muscle response at GM muscle was at FP action.…”
Section: Discussionsupporting
confidence: 89%
“…Trigno sensor was used to detect muscle signal in this study by using sample rate at 1000 Hz. GM muscle was chosen based on literature studies for lower leg implication in driving [14][15]. Before placing the electrode, the belly of the muscle skin was identified by using certain activity as specified by Surface Electromyography for Non-Invasive Measurement (SENIAM) recommendations.…”
Section: Electrical Impedance Myography Analysismentioning
confidence: 99%
“…The relationship between reaction force and perceived force with relation to the control input for the driving interface is provided in Fig. 4(c) [8] [9]. Note that the parameter values of the derived logarithmic curve for the pedal angle were set as a pedal = 59.188, b pedal = −174.68, and for the steering angle were set as a steer = 11.285, b steer = −13.419 by following the procedure presented in II-B.…”
Section: A Setting For Driver Modelmentioning
confidence: 99%
“…Wang et al [7] measured driving posture during pedal operation and explored the relationship between comfort rating of clutch pedal operation and biomechanical parameters such as joint angle, moment, and work. Tanaka et al [8] proved human forceperception characteristics in operating the pedal through a set of perception tests and biomechanical analysis. They reported that the force-perception characteristics is much affected by the contact condition between foot and pedal pad that changes in pedaling operation although dynamic characteristics of the pedal were the same.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation